2020
DOI: 10.1261/rna.077123.120
|View full text |Cite
|
Sign up to set email alerts
|

Expansion segments in bacterial and archaeal 5S ribosomal RNAs

Abstract: The large ribosomal RNAs of eukaryotes frequently contain expansion sequences that add to the size of the rRNAs but do not affect their overall structural layout and are compatible with major ribosomal function as an mRNA translation machine. The expansion of prokaryotic ribosomal RNAs is much less explored. In order to obtain more insight into the structural variability of these conserved molecules, we herein report the results of a comprehensive search for the expansion sequences in prokaryotic 5S rRNAs. Ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…are characterized by the presence of so-called expansion segments (ES), which are additional RNA elements of various sizes incorporated into the universal prokaryotic rRNA core (Gerbi, 1996;Bowman et al, 2020; Figure 1). These ES increase the size and complexity of the respective rRNAs; however, recent analyses have provided evidence for the presence of such ES in both bacteria and archaea (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021). Although most of these sequence additions are limited in size and number (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021), larger ES, similar in size to those commonly observed in eukaryotes, have been recently described in the Asgard archaeal phylum (Penev et al, 2020), which is proposed to be the cradle of the eukaryotic lineage (Spang et al, 2015;Zaremba-Niedzwiedzka et al, 2017;.…”
Section: Ribosomal Subunit Composition: Archaeal Specificity and Common Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…are characterized by the presence of so-called expansion segments (ES), which are additional RNA elements of various sizes incorporated into the universal prokaryotic rRNA core (Gerbi, 1996;Bowman et al, 2020; Figure 1). These ES increase the size and complexity of the respective rRNAs; however, recent analyses have provided evidence for the presence of such ES in both bacteria and archaea (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021). Although most of these sequence additions are limited in size and number (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021), larger ES, similar in size to those commonly observed in eukaryotes, have been recently described in the Asgard archaeal phylum (Penev et al, 2020), which is proposed to be the cradle of the eukaryotic lineage (Spang et al, 2015;Zaremba-Niedzwiedzka et al, 2017;.…”
Section: Ribosomal Subunit Composition: Archaeal Specificity and Common Featuresmentioning
confidence: 99%
“…These ES increase the size and complexity of the respective rRNAs; however, recent analyses have provided evidence for the presence of such ES in both bacteria and archaea (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021). Although most of these sequence additions are limited in size and number (Armache et al, 2013;Penev et al, 2020;Tirumalai et al, 2020;Stepanov and Fox, 2021), larger ES, similar in size to those commonly observed in eukaryotes, have been recently described in the Asgard archaeal phylum (Penev et al, 2020), which is proposed to be the cradle of the eukaryotic lineage (Spang et al, 2015;Zaremba-Niedzwiedzka et al, 2017;. However, a common evolutionary relationshipbased on sequence and/or structure homology-of the larger archaeal and eukaryotic ES could not be established (Penev et al, 2020).…”
Section: Ribosomal Subunit Composition: Archaeal Specificity and Common Featuresmentioning
confidence: 99%
“…At the molecular evolution level and in the course of typically millions to billions of years, component parts are added to growing molecules, which also interact with other molecules to form complexes and higher-order molecular and cellular structure [2]. In RNA, the mere existence of rare expansion segments protruding in the molecules of selected lineages (e.g., bacterial and archaeal 5S rRNA [3]) suggests tendencies of molecular growth. However, accretion must be made explicit with phylogenetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Although helix 44 contributes to the accuracy of translation initiation (Qin et al 2012), the position of 16Gap5 does not affect known functional sites. 5Gap1 in the 5S rRNA corresponds to helix IV and loop D, a region that shows large structural variation in bacteria, and can be lost (Szymanski et al 2016; Stepanov and Fox 2021). Some rRNA helices are known to be deleted in small non-CPR genomes (Nikolaeva et al 2021), but no case of 23SGap3 (the loss of 23S rRNA helix 78) has yet been reported.…”
Section: Resultsmentioning
confidence: 99%